PENGARUH PENGGUNAAN BAHAN DASAR DAN JENIS GULA TERHADAP TEBAL LAPISAN DAN UJI ORGANOLEPTIK NATA SEBAGAI PETUNJUK PRAKTIKUM BIOLOGI KD.2.2 SEMESTER GANJIL KELAS X - Daika Silviana Effendi; Sri Utami (Jurnal Pendidikan, 2013)
Nata is a type of food that contains enough fiber in lieu of fruit. The study aimed to determine the effect of the use of the base material and the type of sugar to a thick layer and organoleptic nata, the results are used as the building blocks of Biology Practical Hints KD.2.2 semester class X. research using completely randomized design ( CRD ) with two factors, namely the use of nata the manufacture and delivery of different types of sugar. At each treatment be repeated 3 times. Organoleptic assessment Nata de Nata de coco leri and performed by 25 panelists using a questionnaire that includes color, firmness, and flavor. Nata thickness data were analyzed using statistical methods annava two lanes and organoleptic test data were analyzed by descriptive qualitative. The data were the average coating thickness showed significant nata, ie the resulting value ( 0.000 ) < significance level ( 0:05 ). Treatments that received the highest layer thickness is G1N2 = 18.32 mm. The thickness of the lowest is the treatment G2N1 = 6.20 mm . Organoleptic test treatments that have the highest value is G2N2 . The lowest value is G3N2 .